NEW MARKETS FOR IDEAS. - Hope, J. William (The Accounting Review, 1953)
Abstract Today, the members of the American Accounting Association have assumed the performance of an important, dual mission. As teachers of accounting they have accepted the responsibility to train young men in the sound accounting theory and practice which will provide the foundation for whatever these men may build during their careers. And as teachers they have the opportunity to influence young men at that time in life when they are forming the habits, attitudes, virtues and vices which are likely to remain with them throughout their lives. To accomplish this dual mission, it is essential that accounting teachers be alive not only to new techniques in education, but to the changing complexity of business and government, and to new developments in accounting theory and practice. Nor is it enough to be aware of such changes. A vital group of teachers not only recognizes change; it causes change. These necessities to progress require primarily the exchange of ideas, for ideas-bartered in the free, competitive forum-are the life-force of any art, including the arts of teaching and of accounting. In this respect the American Accounting Association has played a major role since its organization in 1916.